FOOD AND FEEDING HABITS OF THE HORSE-MACKEREL, CARANX KALLA (CUV. & VAL.) - Kagwade, V N (Indian Journal of Fisheries, 2011)
The importance of the knowledge of food and feeding habits of a fish inunderstanding its fishery biology has been very well established. Often it helps infinding out the seasonal variations in the distribution of a fish species. Sometimesthe rate of feeding has a bearing on the spawning of the fish. The nature of thefood composition of a fish will also throw light on the possible habitats it frequents.Chidambaram and Venkataraman (1946), Chacko and Mathew (1955) andKagwade (1965) have given short accounts of the food of Caranx kalla. Thefood and feeding habits of the different species of the horse-mackerel have beendescribed briefly in the works of Datar (1954), Kuthalingam (1955, '59) andTandon (1960). But for these, there is no other published account on the foodand feeding habits of C. kalla which forms an important component of the fishcatches both on the east and west coasts of India. Hence, an attempt has beenmade here to study this aspect in detail.